Auditory Neural Plasticity in Tinnitus Mechanisms and Management - Kunkun Wang; Dongmei Tang; Jiaoyao Ma; Shan Sun (Neural Plasticity)
Tinnitus, which is the perception of sound in the absence of a corresponding external acoustic stimulus, including change of hearing and neural plasticity, has become an increasingly important ailment affecting the daily life of a considerable proportion of the population and causing significant burdens for both the affected individuals and society as a whole. Here, we briefly review the epidemiology and classification of tinnitus, and the currently available treatments are discussed in terms of the available evidence for their mechanisms and efficacy. The conclusion drawn from the available evidence is that there is no specific medication for tinnitus treatment at present, and tinnitus management might provide better solutions. Therapeutic interventions for tinnitus should be based on a comprehensive understanding of the etiology and features of individual cases of tinnitus, and more high quality and large-scale research studies are urgently needed to develop more efficacious medications.